PD-L2 Is Constitutively Expressed in Normal and Malignant Urothelium - Dowell, Alexander C.; Munford, Haydn; Goel, Anshita; Gordon, Naheema S.; James, Nicholas D.; Cheng, K. K.; Zeegers, Maurice P.; Ward, Douglas G.; Bryan, Richard T. (Frontiers in Oncology, 2021)
The use of immune checkpoint blockade, in particular PD-1 and PD-L1 inhibitors, is now commonplace in many clinical settings including the treatment of muscle-invasive bladder cancer (MIBC). Notwithstanding, little information exists regarding the expression of the alternative PD-1 ligand, PD-L2 in urothelial bladder cancer (UBC). We therefore set out to characterise the expression of PD-L2 in comparison to PD-L1. Firstly, we assessed PD-L2 expression by immunohistochemistry and found widespread expression of PD-L2 in UBC, albeit with reduced expression in MIBC. We further investigated these findings using RNA-seq data from a cohort of 575 patients demonstrating that PDCD1LG2 (PD-L2) is widely expressed in UBC and correlated with CD274 (PD-L1). However, in contrast to our immunohistochemistry findings, expression was significantly increased in advanced disease. We have also provided detailed evidence of constitutive PD-L2 expression in normal urothelium and propose a mechanism by which PD-L2 is cleaved from the cell surface in MIBC. These data provide a comprehensive assessment of PD-L2 in UBC, showing PD-L2 is abundant in UBC and, importantly, constitutively present in normal urothelium. These data have implications for future development of immune checkpoint blockade, and also the understanding of the function of the immune system in the normal urinary bladder.